MCDM Methods for Business and Management - Filipe, J.; Genç, T., (2020)
Nowadays we live in a world of continuous and necessary decisions in every moment of our lives. We have to make choices each moment in scenarios of a multitude of existing conflictual criteria and situations. Life requires ability to decide according to the multiple alternatives that exist in the day-to-day operandi. Recently, multiple criteria models appear in a flourishing position when allocating alternatives to predefined ordered categories considering the defined preference order on criteria scales, becoming MCDM a particularly important subfield of Operations Research and Management Sciences.